La pluripatrimonialisation, conséquence des extensions patrimoniales - Lucas Marolleau (Temporalités)
Our article proposes to deduce from the geohistorical analysis of heritage polarized by the historic center of Bologna (Italy) the successive and simultaneous logics that accompany the temporal evolution of the heritage fact, and thus define what we render by the neologism of “pluripatrimonialization”. To this end, we are conducting a comparative study of the architectural and urban heritage of this area, based on the porticoed sites listed by Unesco as World Heritage Sites in July 2021.This corpus is in fact an opportunity for local player to highlight a typical form of heritage, spread throughout the commune of Bologna, which is part of the local heritage history. Its definition presupposes that they confront both exogenous representations in a context of cultural globalization (Gravari-Barbas, 2012) and the semiogenesis of existing corpora of national and municipal property as legacy and production of meaning (Davallon, 2000; Rautenberg, 2003; Morisset, 2009). The labelled result is thus the product of diachronic relationships with previous patrimonializations and synchronic relationships with the territory and its socio-spatial dynamics. These heritage polytemporalities reveal the multiple extensions of heritage status and the different spatio-temporal strata that constitute an example of pluripatrimonialization.